Spontaneous glioma-induced seizures recorded in a living human brain tissue preparation. (12th October 2019) - Kirby, Alastair; Pedro Lavrador, Jose; Brogna, Christian; Vergani, Francesco; Zebian, Bassel; Chandler, Christopher; Bodi, Istvan; Bhangoo, Ranjeev; Keyoumars, Ashkan; Finnerty, Gerald
Abstract: Gliomas often present clinically with seizures. Tumour-associated seizures can be difficult to control with medication. A deeper understanding of the cellular mechanisms underlying tumour-associated seizures would provide a basis for developing new treatments. Here, we investigate epileptic discharges in peritumoral cortex using living human brain tissue donated by people having a craniotomy for glioma resection (REC approval, 18/SW/002). The brain tissue was cut into thin slices, which preserved the architecture of the glioma and the adjacent healthy brain. The brain slices were incubated in 5-aminolevulinic acid to make the glioma cells fluorescent. This enabled us to make electrophysiological recordings of brain activity across the boundary between glioma and brain. We recorded from brain slices of 5 participants with glioblastoma and 4 participants with oligodendroglioma (WHO grade II – III). Spontaneous "seizure-like" discharges were recorded in brain slices from 5/8 participants (3 GBM, 2 oligodendroglioma) who reported seizures and from one participant (GBM) who had not had any clinical seizures. Further analysis of the seizure-like discharges revealed that they could be subdivided into two distinct types based on the major frequencies in the discharge. We concluded that human brain slices from people with either a low-grade or a high-grade glioma can generate spontaneous seizure-like discharges. The living human brain tissue preparation gives us a platform to study the mechanisms of tumour-associated seizures and how abnormal neural activity affects glioma growth.